Oxygen uptake kinetics and speed-time correlates of modified 3-minute all-out shuttle running in soccer players - Kramer, M.; Du Randt, R.; Watson, M.; Pettitt, R. W. (PLOS ONE, 2018)
How parameters derived from oxygen uptake kinetics relate to critical speed is not fully understood, and how such parameters relate to more sport-specific performances, such as shuttle running, has not been investigated. Therefore, the primary aims of the present student were to examine the kinetics during all-out linear and shuttle running and compare physiological variables of all-out running to variables measured during a graded exercise test (GXT). Fifteen male soccer players performed a graded exercise test (GXT) and the kinetics from a series of three different 3-min all-out tests (3MT`s) were evaluated. achieved during the GXT did not differ from maximal achieved during the all-out tests (F = 1.85, p = 0.13) (overall ICC = 0.65; typical error = 2.48 ml·kg-1·min-1; coefficient of variation = 4.8%). A moderate, inverse correlation (r = -0.62, p = 0.02) was observed between t (14.7 ± 1.92 s) and CS (3.96 ± 0.52 m·s-1) despite the narrow SD for t. No differences (p > 0.05) were observed for any of the kinetics between continuous and shuttle running bouts. The linear running 3MT (r3MT) represents a viable surrogate to the GXT and data beyond CS and D` may be gleaned by using the bi-exponential speed-time model.